Maisie Dobbs Birds of a feather : two novels - Winspear, Jacqueline (New York Quality Paperback Book Club, 2005)
Maisie Dobbs entered domestic service in 1910 at thirteen, working for Lady Rowan Compton. When her remarkable intelligence is discovered by her employer, Maisie becomes the pupil of Maurice Blanche, a learned friend of the Comptons. In 1929, following an apprenticeship with Blanche, Maisie hangs out her shingle: "M. Dobbs, trade and personal investigations." She soon becomes enmeshed in a mystery surrounding The Retreat, a reclusive community of wounded WWI veterans. At first, Maisie only suspects foul play, but she must act quickly when Lady Rowan's son decides to sign away his fortune and take refuge there. Maisie hurriedly investigates, uncovering a disturbing mystery, which, in an astonishing denouement, gives Maisie the courage to confront a ghost that has haunted her for years.
Maisie Dobbs is back and this time she has been hired to find a wealthy grocery magnate's daughter who has fled from home. What seems a simple case at first becomes complicated when Maisie learns of the recent violent deaths of three of the heiress's old friends. Is there a connection between her mysterious disappearance and the murders? Who would kill such charming young women? As Maisie investigates, she discovers that the answers to all her questions lie in the unforgettable agony of The Great War.
Maisie Dobbs -- Birds of a feather.
Originally published: New York: Soho, 2003.
"Two novels."
Keywords: Dobbs, Maisie (Fictitious character); Women private investigators -- England; Detective and mystery stories